Animal defense strategies and anxiety disorders - Rosana Shuhama; Cristina Marta Del‐Ben; S.R. Loureiro; Frederico Guilherme Graeff (2007)
Anxiety disorders are classified according to symptoms, time course and therapeutic response. Concurrently, the experimental analysis of defensive behavior has identified three strategies of defense that are shared by different animal species, triggered by situations of potential, distal and proximal predatory threat, respectively. The first one consists of cautious exploration of the environment for risk assessment. The associated emotion is supposed to be anxiety and its pathology, Generalized Anxiety Disorder. The second is manifested by oriented escape or by behavioral inhibition, being related to normal fear and to Specific Phobias, as disorders. The third consists of disorganized flight or complete immobility, associated to dread and Panic Disorder. Among conspecific interactions lies a forth defense strategy, submission, that has been related to normal social anxiety (shyness) and to Social Anxiety Disorder. In turn, Posttraumatic Stress Disorder and Obsessive-Compulsive Disorder do not seem to be directly related to innate defense reactions. Such evolutionary approach offers a reliable theoretical framework for the study of the biological determinants of anxiety disorders, and a sound basis for psychiatric classification.